A strong phase separation polyurethane for self-repairing large-scale damage. Issue 25 (14th June 2022) - Li, Mengyu; Han, Xin; Fan, Zewen; Chen, Hao; Zhang, Yu; Zhang, Lin; Guo, Dan; Xie, Guoxin
Abstract : We report a self-repairing polyurethane material with targeted repair effects on large-scale damage with a width of over 1 mm, which can be used to solve the problems of component failure caused by the damage of conventional coatings. Abstract : Self-repairing materials with high strength can repair cracks easily but are unable to repair large-scale damage because high strength and self-repair effects on large-scale damage are mutually exclusive; as a result, their performance hardly supports the purpose for which they can be commercialized. Therefore, the development of high-strength materials that are capable of self-repairing large-scale damage is an important area of research. Here, we report a self-repairing polyurethane material with targeted repair effects on large-scale damage with a width of over 1 mm. The notable self-repair effect on the large-scale damage of the prepared high-strength materials is controlled by the disordered hydrogen bonds within polyurethane chain segments. The targeted repair effect that can be initiated by temperature is induced by the difference between the internal and external chemical components of the polyurethane. The changes in the molecular configuration caused by the synergistic dynamic bond structure give rise to the targeted and large-scale damage self-repairing effects. This strategy of using the asymmetric synergistic molecular structure provides a new design approach for commercial self-repairing materials that can further extend the service life of commercial polymeric materials.